Modyfikacja stanowiska i metodyki pomiaru parametrów rozpylonej strugi cieczy = The modyfication of set-up and methodology of the measurment of parameters of atomized liquid stream - Ochowiak, Marek; Krupińska, Andżelika; Włodarczak, Sylwia; Markowska, Małgorzata (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The aim of this paper is to present the measurement methodology using a modified experimental set-up allows for the aerosol characteristic determination. Adaptation of the set-up allows for the simultaneous determination of the droplet diameters, droplet size distribution (radial and volume), and the spray angle.
Keywords: rozpylona struga cieczy; systemy pomiarowe; metodyka pomiarów